Nuclear fusion in the deuterated cores of inflated hot Jupiters - Ouyed, Rachid; Jaikumar, Prashanth (Astrophysics and space science, 2016)
Ouyed et al. (Astrophys. J. 501:367, 1998 ) proposed Deuterium (DD) fusion at the core-mantle interface of giant planets as a mechanism to explain their observed heat excess. But rather high interior temperatures ( ∼ 10 5 K ) and a stratified D layer are needed, making such a scenario unlikely. In this paper, we re-examine DD fusion, with the addition of screening effects pertinent to a deuterated core containing ice and some heavy elements. This alleviates the extreme temperature constraint and removes the requirement of a stratified D layer. As an application, we propose that, if their core temperatures are a few times 10 4 K and core composition is chemically inhomogeneous, the observed inflated size of some giant exoplanets (“hot Jupiters”) may be linked to screened DD fusion occurring deep in the interior. Application of an analytic evolution model suggests that the amount of inflation from this effect can be important if there is sufficient rock-ice in the core, making DD fusion an effective extra internal energy source for radius inflation. The mechanism of screened DD fusion, operating in the above temperature range, is generally consistent with the trend in radius anomaly with planetary equilibrium temperature T eq , and also depends on planetary mass. Although we do not consider the effect of incident stellar flux, we expect that a minimum level of irradiation is necessary to trigger core erosion and subsequent DD fusion inside the planet. Since DD fusion is quite sensitive to the screening potential inferred from laboratory experiments, observations of inflated hot Jupiters may help constrain screening effects in the cores of giant planets.